Pengembangan Sistem Informasi Akademik Pada Sekolah Dasar Islam Terpadu Insantama (SDIT) Malang Berbasis Website - Andra Pargiyani; Bayu Priyambadha; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Integrated Islamic elementary school of Malang is an elementary school with the concept of Islamic boarding school. But, there are drawbacks in school management that needs to be improved, such as teachers still using Microsoft Excel to input values of student assessment. Besides that, there are another proble arises in the tuition payment service. Records that have not been computerized sometimes caused by human error. To overcome those problems, an academic information system is needed to improve the service to teachers and parents effectively in terms of getting the results of student grades while facilitating teachers in input value, give convenience to administration units to update payment information directly and give parents access rights to interact with the homeroom teacher. This study uses the waterfall model as a software development model and is built using a codeigniter framework that supports mvc (models, views and controllers) and uses javascript. The system has been successfully tested with blackbox testing on unit testing and whitebox testing on validation testing and non-functional testing namely compatibility testing.